Trust Games and Beyond - Alós-Ferrer, Carlos; Farolfi, Federica (Frontiers in Neuroscience, 2019)
Trust is fundamental for the stability of human society. A large part of the experimental literature relies on the Trust Game as the workhorse to measure individual differences in trust and reciprocity. In this review we highlight the difficulties and limitations of this popular paradigm, as well as the relations to alternative instruments ranging from survey measures to neurochemical manipulations and neuroimaging.